Victorian Museums and Victorian Society - Woodson-Boulton, Amy (History compass, 2008)
This article explores how the study of museums intersects with key aspects of Victorian historiography. A large scholarship on museums has developed as part of the larger, multidisciplinary effort to understand modernity in general, and Victorian society in particular, in terms of power, culture, and imperialism. Deeply influenced by the works of Michel Foucault and Pierre Bourdieu, Museum Studies has tended to emphasize the cultural and social power of ‘the museum’. However, more recent works have shown that when viewed in their particular historical contexts, museums seem far less powerful, and the class whose interests they apparently serve seems far less unified, than scholars originally imagined. Proliferating during a period of intense social transformation, Victorian museums ultimately both celebrated the new dogma of progress and hoped to mitigate the worst effects of urbanization, industrialization, and capitalism. A close study of the interconnections between Victorian museums and Victorian society thus illuminates two essential Victorian contradictions: the optimistic, imperial, industrial, capitalist society that contained its own critique, and the search for the transcendent in the material.